Post-Earthquake Damage Assessment after the 6.5 Mw Earthquake on December, 7th 2016 in Pidie Jaya, Indonesia. Issue 1 (2nd January 2022) - Idris, Yunita; Cummins, Phil; Rusydy, Ibnu; Muksin, Umar; Syamsidik,; Habibie, Mohammad Yoza; Meilianda, Ella
ABSTRACT: This paper presents a post-earthquake damage assessment of the 6.5 Mw earthquake in Pidie Jaya, Indonesia which occurred on December, 7th 2016. The earthquake killed 112 people and caused the collapse of about 3000 buildings. The assessment started on the day after the earthquake. The survey covered nine sub-districts of Pidie Jaya regency in the Province of Aceh, northern Sumatra. The post-event damage assessment was conducted by a team of researchers from Syiah Kuala University and local authorities. The damage survey assessed the damage levels of residential houses, school buildings and markets. The most common construction damages reported in this article are failures of reinforced concrete, confined masonry and timber structures. The ground motion field was modeled using Openquake application and the site response employed Vs30 values inferred from topography. This calculated ground motion was compared to data from post-earthquake field assessment reports. The highest percentage of heavy damage was recorded in the area of the fault rupture and along the shorelines area. The types of failure observed are summarized in the context of Indonesian construction practice, with particular reference to the seismic resilience of the Rumoh Aceh traditional wood construction.